IDEAS FOR ADVANCING MATHEMATICALLY PRECOCIOUS YOUTH: A REVIEW OF THE LITERATURE - Tello, Brian Pablo (Acta Scientiae et Intellectus, 2024)
Mathematically Precocious Youth (MPY) are taught in a variety of ways in American educational system. This literature review paper explored which educational options may be best for MPY and the nation and reviewed many of the educational options available for MPY. The goal was to find which educational options provided MPY the best chance to be successful in school and beyond. The paper found many MPY were not being taught at the correct level and were not provided enough challenging material. MPY found great educational success as well as career success from acceleration programs, computer-based and distant learning courses, and mathematical competitions. The paper concluded acceleration set at the right level and pace was the best option to help MPY find educational success.